Visual and refractive outcomes of opposite clear corneal incision combined with rotationally asymmetric multifocal intraocular lens implantation - Qin, Xiaoyu; Yao, Pengxiang; Wu, Xinyuan; Wu, Yang; Hong, Yufang; Chen, Zhenzong; Yuan, Yuanzhi (Frontiers in Medicine, 2024)
Purpose: To evaluate the visual and refractive outcomes of astigmatic cataract patients following opposite clear corneal Incision (OCCI) combined with rotationally asymmetric multifocal intraocular lens (IOL) implantation. Setting: Department of Ophthalmology, Zhongshan Hospital (Xiamen), Fudan University, People's Republic of China. Design: Retrospective cohort study Methods: This study comprised 58 cataract eyes of 54 patients with corneal astigmatism who underwent phacoemulsification and rotationally asymmetric multifocal IOL implantation which received either OCCI (OCCI group) or a single clear corneal incision (SCCI group). The follow-up period was 3 months after surgery. Distance, intermediate and near visual acuity, refractive outcomes, and corneal anterior keratometry were compared between the two groups. Vector analysis was used to evaluate astigmatism correction. Results: Three months after surgery, the distance, intermediate and near visual acuity, and sphere remained comparable between the two groups, but a significant difference was detected in residual astigmatism and anterior corneal keratometric astigmatism. In the OCCI group, the residual astigmatism and keratometric astigmatism were -0.60±0.29 D and 0.59±0.28 D, respectively, which were lower than those in SCCI groups ( -1.18±0.47 D and 1.15±0.45 D, both p<0.05). In vector analysis, the difference vector (DV), angle of error (AoE), Absolute AoE, Index of Success (IoS) and correction index (CI) were statistically significantly different between the two groups (p<0.05). Conclusions: OCCI combined with rotationally asymmetric multifocal intraocular lens implantation showed predictable and desirable efficacy in treating cataract patients with astigmatism.